2022
DOI: 10.1155/2022/7883945
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between the Intestinal Virome and Other Components of the Microbiota, and Its Effect on Intestinal Mucosal Response and Diseases

Abstract: In recent years, there has been ample evidence illustrating the effect of microbiota on gut immunity, homeostasis, and disease. Most of these studies have engaged more efforts in understanding the role of the bacteriome in gut mucosal immunity and disease. However, studies on the virome and its influence on gut mucosal immunity and pathology are still at infancy owing to limited metagenomic tools. Nonetheless, the existing studies on the virome have largely been focused on the bacteriophages as these represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 208 publications
0
5
0
Order By: Relevance
“…Until the last decade, while the bacterial composition of the microbiome has received considerable attention, relatively little was known about the composition and physiological significance of the human gut phage. This knowledge gap was chiefly due to the limited tools and technical means available (Clinton et al, 2022). Gut viromes can only be identified using traditional culture-based methods followed by microscopy techniques such as transmission electron or epifluorescence microscopy.…”
Section: Characteristics and Composition Of The Intestinal Phageomementioning
confidence: 99%
See 1 more Smart Citation
“…Until the last decade, while the bacterial composition of the microbiome has received considerable attention, relatively little was known about the composition and physiological significance of the human gut phage. This knowledge gap was chiefly due to the limited tools and technical means available (Clinton et al, 2022). Gut viromes can only be identified using traditional culture-based methods followed by microscopy techniques such as transmission electron or epifluorescence microscopy.…”
Section: Characteristics and Composition Of The Intestinal Phageomementioning
confidence: 99%
“…For example, the proximal gut presents a microaerophilic environment that fosters bacterial families like Lactobacillaceae and Enterobacteriaceae, while the distal gut, being anaerobic, allows Bacteroidaceae, Prevotellaceae, and Ruminococcaceae to thrive (Donaldson et al, 2016). This environmental gradient likely affects phage distribution and abundance, with empirical evidence from primate and porcine models showing site-specific variations in phage abundance and composition within the gastrointestinal tract (Looft et al, 2014;Zhao et al, 2019;Clinton et al, 2022). Phage populations also vary cross-sectionally through the gut's mucus layers, which may have further implications for the Immune System (Tetz et al, 2017).…”
Section: Characteristics and Composition Of The Intestinal Phageomementioning
confidence: 99%
“…Phages indirectly fuel the immune response through the release of bacterial products following bacterial lysis or translocation across the epithelium (transcytosis), activating pattern recognition receptors on the intestinal epithelial cells or resident immune cells [77]. In addition, specific virome-derived factors can interfere with barrier integrity and impact intestinal physiology, often through interaction with other commensals [78]. For example, Sinha et al pooled viral-like particles (VLPs) from three UC patients, mainly enriched in Microviridae phages and, to a lesser extent in crAss-like, Siphoviridae, and Podoviridae phages, and transplanted them into human microbiota-associated mice [79].…”
Section: Viruses In Ibdmentioning
confidence: 99%
“…Microbiota include bacteria, archaea, protists, fungi, and viruses, and in human species, they reside on or in the host cells of the oropharynx and lower respiratory tract, gastrointestinal tract, skin, urogenital tract, and possibly other undetected sites [28]. Although viruses in the human microbiota have received less research attention, there has been a recent increasing interest in the virome in the gut and other sites [29][30][31][32]. Studies on the human virome have revealed that bacteria in the microbiota of the host live with viruses, that is, bacteriophages.…”
Section: Viruses and Microbiotamentioning
confidence: 99%
“…Overproduction of toxic materials by dysbiotic microbes, vulnerability to invasion by microbes through weakened mucosal barriers, and disruption of the homeostatic relationship between microbiota and the host immune system, including the development and function of the immune system, have been suggested to be associated with disease [35][36][37]. Dysbiotic states of viruses in the microbiota may also play crucial roles in host immunological, biological, and metabolic homeostasis, and may be related to the development and progression of some diseases [29][30][31][32].…”
Section: Viruses and Microbiotamentioning
confidence: 99%